The feasibility of using high resolution genome sequencing of influenza A viruses to detect mixed infections and quasispecies. - Muthannan A Ramakrishnan; Zheng Jin Tu; Sushmita Singh; Ashok K Chockalingam; Marie R Gramer; Ping Wang; Sagar M Goyal; My Yang; David A Halvorson; Srinand Sreevatsan (PLoS ONE)
Background The rapidly expanding availability of de novo sequencing technologies can greatly facilitate efforts to monitor the relatively high mutation rates of influenza A viruses and the detection of quasispecies. Both the mutation rates and the lineages of influenza A viruses are likely to play an important role in the natural history of these viruses and the emergence of phenotypically and antigenically distinct strains. Methodology and principal findings We evaluated quasispecies and mixed infections by de novo sequencing the whole genomes of 10 virus isolates, including eight avian influenza viruses grown in embryonated chicken eggs (six waterfowl isolates - five H3N2 and one H4N6; an H7N3 turkey isolate; and a bald eagle isolate with H1N1/H2N1 mixed infection), and two tissue cultured H3N2 swine influenza viruses. Two waterfowl cloacal swabs were included in the analysis. Full-length sequences of all segments were obtained with 20 to 787-X coverage for the ten viruses and one cloacal swab. The second cloacal swab yielded 15 influenza reads of approximately 230 bases, sufficient for bioinformatic inference of mixed infections or quasispecies. Genomic subpopulations or quasispecies of viruses were identified in four egg grown avian influenza isolates and one cell cultured swine virus. A bald eagle isolate and the second cloacal swab showed evidence of mixed infections with two (H1 and H2) and three (H1, H3, and H4) HA subtypes, respectively. Multiple sequence differences were identified between cloacal swab and the virus recovered using embryonated chicken eggs. Conclusions We describe a new approach to comprehensively identify mixed infections and quasispecies in low passage influenza A isolates and cloacal swabs and add to the understanding of the ecology of influenza A virus populations.